Teden dni pod cincalijami z Milkom Matičetovim - Novak, Vilko (Traditiones (Ljubljana), 1999)
In 1950 the author took his colleagues and friend Milko Matičetov and Boris Orel to Prekmurje, the land of his birth. In his article he remembers those cool winter days during which Milko Matičetov recorded his first field observations on the culture of people from the Prekmurje villages
Keywords: Matičetov, Milko, 1919-; ethnology; etnologija; biografije